PERAN E-WALLET DALAM PENGAMBILAN KEPUTUSAN YANG EFISIEN - Hermawan, Arfindo; Gloria, Angelica Cristy; Yunari, Syahna Shinta; Pandin, Maria Yovita R. (LPPM Universitas Bina Bangsa, 2024)
This rapid technological progress has made many changes, such as in the current era, developments have made many changes in carrying out transactions such as digital wallets (e-wallets). This e-wallet has many advantages in making it easier for us to save money, carry out transactions and manage our daily finances digitally via smartphone in a practical and time efficient way to use it. The aim is to analyze the role of e-wallets which will influence efficient financial decisions among students of the 4th semester accounting study program at Widya Mandala Catholic University Surabaya 2024. The method used in this research is qualitative using respondents as data collectors. The total population of the objects we studied was 97 respondents, then we used the Slovin formula where the results of our calculations found that the number of respondents we had to research was 78 respondents. By compiling 5 questions, they were used as research objects. The results of the analysis show that e-wallets make financial management easier by recording all transactions in a position where of course e-wallets will provide efficiency in financial recording so that respondents or users don't have to bother recalculating their money manually. However, there are still some privacy issues and even fraud in certain circles which can be a point of view for all e-wallet companies to be able to anticipate this. The convenience and comfort provided by digital payments via e-wallet is present and felt by consumers when carrying out transactions and this can be a source of satisfaction for users. There are also shortcomings such as respondents not feeling any change in behavior because respondents have not felt any change in behavior due to lack of access or understanding of technology, to a preference for traditional payment methods